Exploring the Potential Role of Sophora alopecuroides L. in Inflammation of Bovine Mammary Epithelial Cells Induced by Lipoteichoic Acid Based on Network Pharmacology and Experimental Validation - Yuan, Ziwen; Li, Fang; Zhang, Wenfei; Wei, Yanming; Hua, Yongli (Combinatorial Chemistry & High Throughput Screening, 2025)
AimThis study aimed to investigate the anti-inflammatory effect and mechanism of Sophora alopecuroides L. (KDZ) on lipoteichoic acid (LTA)-induced inflammation in Bovine Mammary Epithelial Cells (BMEC).MethodsThe KDZ active ingredient database was established by using ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) to detect the chemical components of KDZ and combine it with the TCMSP database. Furthermore, potential targets of KDZ active ingredients were collected through the UniProt database, and mastitis-related targets were screened through the OMIM, Genecard, and DisGeNET databases. Furthermore, common targets were identified between ingredient targets and disease targets, and protein-protein interaction analysis was performed on them using the STRING platform. Furthermore, the protein interaction network was constructed using Cytoscape software. Core targets were screened through network topology analysis. On this basis, GO and KEGG enrichment analyses were performed on the common target, and molecular simulation docking analysis was conducted on the main active ingredients and core targets. Finally, the accuracy of the network analysis results was validated using in vitro cell experiments.ResultsThe results of UPLC-QTOF-MS detection and network pharmacology analysis showed that KDZ could intervene in signaling pathways, such as the IL-17 signaling pathway, TNF signaling pathway, MAPK signaling pathway, etc., by acting on 80 common targets through 15 potential active ingredients, thereby regulating biological processes, such as positive regulation of peptidyl serine physiology, apoptotic process, and inflammatory response, to treat mastitis. Besides, molecular simulation docking analysis also showed that the main active ingredients in KDZ, such as quercetin, matrine, calycosin, etc., can form stable bindings with 11 core targets (TNF-α, IL-6, IL-1β, etc.) through hydrogen bonding. Further in vitro validation experiments confirmed that KDZ intervention could inhibit the IL-17 signaling pathway by inhibiting the expression of GSK3β and subsequently inhibiting the production of downstream inflammatory cytokines IL-8, IL-6, IL-1β, and TNF-α, thereby alleviating LTA-induced BMEC inflammatory damage.ConclusionKDZ can alleviate LTA-induced BMEC inflammatory damage by inhibiting the IL-17 signaling pathway. This study can provide a scientific basis for the clinical application of KDZ and lay the foundation for the development of new therapeutic drugs for mastitis.
Keywords: Sophora alopecuroides L.